Critical Introduction To Visual Culture Artists: Navigating Postmodernism and Deconstruction in Artistic Expression - Muhammed Sufiyan V.V (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
This abstract offers a comprehensive overview of a critical introduction to visual culture artists within the framework of postmodernism and deconstruction. It delves into how these influential theoretical paradigms have reshaped artistic creation, interpretation, and cultural discourse in the contemporary visual landscape. The study explores the intricate relationship between visual culture artists and the concepts of postmodernism and deconstruction, which challenge established norms, meanings, and hierarchies. Through an interdisciplinary approach, it investigates how artists engage with these frameworks, deconstructing traditional boundaries and reimagining artistic practice. By analyzing key works and artists, the abstract illustrates how postmodernist and deconstructive strategies dismantle grand narratives, blur the lines between reality and representation, and prompt a reevaluation of artistic intent. Emphasizing the role of ambiguity, intertextuality, and cultural context, this exploration showcases how visual culture artists incorporate postmodernist and deconstructive elements to provoke critical dialogue and challenge viewer assumptions. The abstract examines the impact of these movements on diverse art forms, from painting and sculpture to multimedia installations and digital art, showcasing the evolution of artistic techniques and themes. Furthermore, the study delves into the implications of postmodernism and deconstruction on the viewer's role, highlighting the participatory nature of interpretation and the destabilization of fixed meanings. It also addresses the challenges and controversies that arise when artists navigate ethical concerns, cultural appropriation, and the commodification of art in the postmodern era. In summary, this abstract encapsulates the essence of a critical introduction to visual culture artists through the lenses of postmodernism and deconstruction. It invites scholars, students, and art enthusiasts to explore the transformative potential of these paradigms in reshaping artistic landscapes and fostering a deeper understanding of the complex relationships between art, culture, and society.